PERFORMANCE IMPROVEMENT STRATEGY PALANGKA RAYA CITY MINIBUS WITH QUALITY FUNCTION DEPLOYMENT (QFD) METHOD - Airways Parlindungan Siahaan; Nadia Pretty Excesia (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
Palangka Raya, which has a population of 298,950 people in 2021, has experienced a population increase of 2.78% from the previous year. This rate of population growth will have a major impact on population mobility and the number of people using private vehicles. City transportation is a type of special passenger public transportation that operates in the City of Palangka Raya and serves urban areas. There are 5 (five) fixed routes that will be examined in this study, namely routes served by city transportation A, B, C, E, and F in the City of Palangka Raya. This research will use the CSI (Customer Satisfaction Index) and QFD (Quality Function Deployment) methods to determine the increase in the operational performance of city transportation. Based on CSI (Customer Satisfaction Index) analysis, the existing fleet must be modernized because this is a suggestion from the Quality Function Deployment based on the HOQ matrix.